Mathematical quest as the way of increase of motivation of students to studying to the higher mathematics - Irina N. Bulanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In article one of possible techniques of teaching the higher mathematics in technical college is considered. The higher mathematics - a difficult subject. The fear of it often complicates digestion of material whereas the positive spirit opposite, helps to deal with objectives. The game element in any business promotes manifestation of interest and more active inclusion in process. Modern young people are keen on various computer games. The course of the higher mathematics fits the definition of a quest - adventure game which cornerstone research of the world by means of the solution of the puzzles and tasks demanding from the player of intellectual efforts is. The invitation of students in a fascinating mathematical adventure can change their relation to a subject, cause interest, strengthen motivation and, as a result, increase the level of digestion of material.